Klebsiella pneumoniae sacroiliac septic arthritis: First case report - Chee, Yong Chuan (IDCases, 2018)
Infective sacroiliitis is a rare disease with misleading clinical signs that often delay diagnosis. We report a case of pyogenic sacroiliac joint septic arthritis caused by Klebsiella pneumoniae that has not been reported in the literature highlighting its importance especially among diabetics.